COVID-free surgical pathways for treating patients with acute calculous cholecystitis: a retrospective comparative study - Giacopelli, Pietro; Cristaudi, Alessandra; Majno, Pietro; Roesel, Raffaello; Iaquinandi, Fabiano; Mongelli, Francesco (Frontiers in Surgery, 2024)
Introduction: During the Sars-Cov-2 crisis, some of the resources committed to emergency surgery services were transiently reallocated to the care of patients with severe Covid-19, preserving immediate treatment of mostly non-deferrable conditions. Moreover, the fear of contracting infections or hindering the treatment of critical Covid-19 patients has caused many individuals to defer seeking emergency care. This situation has then possibly modified the standard of care of some common surgical conditions and the relative outcomes. Our aims was to highlight any difference in surgical outcomes in patients treated for acute cholecystitis before and during the Covid-19 outbreak.Method:This is a retrospective study on a prospectively collected database that included all consecutive patients treated for acute cholecystitis from March 2019 to February 2021 at the Lugano Regional Hospital, a covid-free hospital for general surgery patients. Patients were divided into preand post-Covid-19 outbreak groups. We collected thorough clinical characteristics and intra-and postoperative outcomes.Results: We included 124 patients, of which 60 and 64 were operated on before and after the Covid-19 outbreak respectively. The two groups resulted similar in terms of patients' clinical characteristics (age, gender, body mass index, ASA score, and comorbidities). Patients in the post-outbreak period were admitted to the hospital 0.7 days later than patients in the pre-outbreak period (3.8±6.0 days vs. 3.1±4.1 days, p=0.453). Operative time, recovery room time, complications, and reoperations resulted similar between groups. More patients in the post-outbreak period received postoperative antibiotic therapy (63.3% vs. 37.5%, p=0.004) and for a longer time (6.9±5.1 days vs. 4.5±3.9 days, p=0.020). No significant histopathological difference was found in operatory specimens.Discussion: Despite more frequent antibiotic therapy that suggests eventually worse inflammatory local status, our results showed similar outcomes for patients treated for acute cholecystitis before and during the Covid-19 pandemic.The local Covid management, reallocating resources, and keeping Covid-free hospitals was key to offering patients a high standard of treatment.